2017
DOI: 10.1016/j.bbmt.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

National Institutes of Health Hematopoietic Cell Transplantation Late Effects Initiative: The Immune Dysregulation and Pathobiology Working Group Report

Abstract: Immune reconstitution following hematopoietic stem cell transplantation (HCT) beyond one year is not completely understood. Many transplant recipients who are free of graft versus host disease (GVHD) and not receiving any immunosuppression more than a year after transplant seem to be able to mount appropriate immune responses to common pathogens and respond adequately to immunizations. However, two large registry studies over the last two decades seem to indicate that infection is a significant cause of late m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 157 publications
0
43
0
2
Order By: Relevance
“…Retrospective data suggest that the immune responses to the MCV4 vaccine are poor after HCT and that a 2-dose regimen may be required to achieve protective antibody titers 6 ; however, the immunogenicity of a single-or multiple-dose vaccine regimen has not been prospectively evaluated. Given the knowledge gaps regarding the safety and immunogenicity of MCV4 after HCT, 7 we conducted a vaccine response study among adult HCT recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective data suggest that the immune responses to the MCV4 vaccine are poor after HCT and that a 2-dose regimen may be required to achieve protective antibody titers 6 ; however, the immunogenicity of a single-or multiple-dose vaccine regimen has not been prospectively evaluated. Given the knowledge gaps regarding the safety and immunogenicity of MCV4 after HCT, 7 we conducted a vaccine response study among adult HCT recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal immune reconstitution has been operationally defined as the restoration of functional pathogen-specific immunity and establishment of anticancer immunity without dysregulation by GVHD and/or HCT-associated autoimmunity [18]. Factors influencing immune reconstitution include age, underlying disease, immunosuppressive state, prior infections, conditioning regimen, donor type, degree of match, stem cell source, immunosuppression, anti-infective practice, GVHD, viral infections, and therapies to prevent relapse [5963].…”
Section: Potentially Lethal Late Effectsmentioning
confidence: 99%
“…To address delayed infectious mortality, it is critical to understand the pathogens responsible, the risk factors, and immunologic correlates. A long-term, multicenter, prospective study with samples collected for immunologic testing has been identified as a critical priority [18]. Such a study will also allow, as an adjunct, the measurement of microbiota changes after HCT and the association of such changes with late infections and immunity.…”
Section: Potentially Lethal Late Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is becoming evident that the timing of vaccination would be more appropriately based on each patient's capacity to respond to vaccine antigens. Evolving data suggest that such immune responses can be measured . However, a more detailed analysis is required prior to developing novel vaccine schedules to better guide effective vaccination post‐alloHSCT.…”
Section: Introductionmentioning
confidence: 99%